2010
DOI: 10.1039/b9nj00630c
|View full text |Cite
|
Sign up to set email alerts
|

A facile synthesis of Ag nanoparticles for mercury ion detection with high sensitivity and selectivity

Abstract: A facile one-step synthesis of Ag nanoparticles (NPs) with particle sizes less than 5 nm is presented. The average size, size distribution and morphology of the NPs were determined using a number of techniques, including UV-visible absorption spectroscopy, transmission electron microscopy, energy-dispersive X-ray spectroscopy (EDX) and a particle size analyzer (PSA). Furthermore, the resulting Ag NPs, without extra treatment, could be used as a probe to detect Hg(II) ions in aqueous media. The response in abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Room temperature synthesis routes for the fabrication of Ag nanoparticles have been investigated recently, showing promising application feasibility and reliability for largescale manufacture with energy saving and safety. Zhang et al [5] and Huang et al [6] prepared Ag nanoparticles at room temperature, showing excellent antibacterial properties; Li et al [22] prepared Ag nanoparticles at room temperature, which was confirmed to be effective for detecting mercury ion with high sensitivity and selectivity; snowflake-like dendritic Ag Nanostructures [23] and Ag nanowires [24] were also prepared at room temperature. As the concept of "green methods" has become more and more important since the last decade [6], nanomaterials scientists start to pay more attention to facile, safe, and environmentally friendly routes for synthesizing Ag nanoparticles, and room temperature is one of the most promising routes to realize this goal.…”
Section: Introductionmentioning
confidence: 99%
“…Room temperature synthesis routes for the fabrication of Ag nanoparticles have been investigated recently, showing promising application feasibility and reliability for largescale manufacture with energy saving and safety. Zhang et al [5] and Huang et al [6] prepared Ag nanoparticles at room temperature, showing excellent antibacterial properties; Li et al [22] prepared Ag nanoparticles at room temperature, which was confirmed to be effective for detecting mercury ion with high sensitivity and selectivity; snowflake-like dendritic Ag Nanostructures [23] and Ag nanowires [24] were also prepared at room temperature. As the concept of "green methods" has become more and more important since the last decade [6], nanomaterials scientists start to pay more attention to facile, safe, and environmentally friendly routes for synthesizing Ag nanoparticles, and room temperature is one of the most promising routes to realize this goal.…”
Section: Introductionmentioning
confidence: 99%
“…The luminescence enhancement displayed a linear range of Hg(II) concentration from 0 to 180 nM with a correlation coefficient of 0.997 (Figure S8 (ESI†)), indicating the potential capability of this system in quantitative analysis of Hg(II). Notably, a limit of detection (LOD) for Hg(II) was calculated to be 5 nM according to the equation C lim  = 3δ/ k , which is lower than the maximum permissible level (10 nM) of Hg(II) in drinking water specified by the U.S. Environmental Protection Agency (EPA) 7, 46 . Additionally, the sensitivity of this proposed method is also found to be comparable to other reported methods for Hg(II) detection as summarized in Table S2 (ESI†) 68, 12, 13, 17,1922, 4753 .
Figure 5( a ) Luminescence emission spectra of 1.0 μM complex 1 in Tris-HNO 3 buffer solution (pH 7.0) containing 0.4 μM Ag nanoparticles and different concentrations of Hg(II) (from bottom to top: 0, 20, 40, 60, 80, 100, 120, 140, 160, 180, 220, 270, 360, and 520 nM).
…”
Section: Resultsmentioning
confidence: 99%
“…Among them, silver nanoparticle (AgNP) has been extensively studied due to their beneficial catalytic, electrical, optical and properties [16][17][18]. With the vast progress of awareness in the field of nanotechnologies and the spectral theories, the luminescence properties of metal NP have also been testified [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%